PSPACE-completeness of majority automata networks - Eric Goles; Pedro Montealegre; Ville Salo; Ilkka Törmä (ELSEVIER SCIENCE BV, 2022)
We study the dynamics of majority automata networks when the vertices are updated according to a block sequential updating scheme. In particular, we show that the complexity of the problem of predicting an eventual state change in some vertex, given an initial configuration, is PSPACE-complete. (C) 2015 Elsevier B.V. All rights reserved.